Juvenile Idiopathic Arthritis and Exercise - Pınar Kısacık; Edibe Ünal (Hacettepe University, 2016)
Arthritis, pain, muscle weakness, bone tissue defficiency, growth and developmental deficits, functional loss and inactivity are the most important problems in children with juvenile idiopathic arthritis. However, it is stated that the growing physical inactivity over time, leads fatigue, muscle weakness and dysfunction, bone resorbtion and motor control deficiency. The physical exercise has an important role in solving all these problems . The exercise protocols in literature diversified in terms of duration, frequency, time, intensity, environment and type/composition. In all studies, it was reported that exercise improves joint swelling, pain scores, range of motion, muscle strength , aerobic capacity, functional ability and quality of life. In conclusion, the optimal exercise program for children with juvenile idiopathic arthritis should be combined with aerobic and neuromuscular training. Besides that, it should be aimed reducing pain and biopsychosocial models with active participation of child, and provided functional and developmental support. The child should be encouraged to participate in recreational and sports activities, so that exercise plan should be integrated in to life plan.